ANALISIS KREDIT BERMASALAH, TINGKAT SUKU BUNGA DAN PROFITABILITAS PADA PT BANK PERKREDITAN RAKYAT (BPR) KCP LIMBANANG KABUPATEN LIMA PULUH KOTA - Sari, Selvi Yona; Pratama, Muahammad Putra (Universitas Putra Indonesia YPTK Padang, 2018)
This study aims to analyze problem loans, interest rates, and the impact on interest income in PT Bank Perkreditan Rakyat (BPR) KCP Limbanang, Lima Puluh Kota District. The research variables are Problematic Credit (x1), Interest Rate (x2), and Profitability (y). Based on the results of this study can be concluded that the level of nonperforming loans that occur at the Bank Perkreditan Rakyat (BPR) KCP Limbanang District Lima Puluh Kota from 2011-2012 the level of non-performing loans decreased compared to the previous year, it means the credit situation is getting better. The interest rate at Rural Bank of KCP Limbanang of Lima Puluh Kota District in 2011-2015 experienced fluctuations in the proof of the highest interest rate in 2011 and the lowest interest rate in 2015. Due to total assets in Rural Bank (BPR) KCP Limbanang District Lima Puluh Kota each year experienced a significant increase whereas profitability from the year 2011-2015 that experienced ups and downs of profitability, this is influenced by the rearrangement of terms and conditions of credit Rural Bank (BPR) KCP Limbanang District Fifty Cities.Finally, the authors suggest to Rural Credit Bank (BPR) Limbanang Kabupaten Lima Puluh Kota The level of nonperforming loans that occur in Rural Banks (BPR) KCP Limbanang District Lima Puluh Kota which continues to fall every year and also problem loans also below the maximum 5% have a positive impact on the bank, as well as an achievement for the bank as it can minimize nonperforming loans and due to improved supervision of good credit disbursement